Artsteps.com sebagai Media Apresiasi Karya Foto - Muhammad Hilmy Ashshiddiq; Kiki Zakiah Darmawan (UNISBA Press, 2022)
Abstract. This research is based on the development of the internet which is supported by the Covid-19 pandemic. In this case, KMJ UNISBA held a virtual photo exhibition. The media used is the website from ArtSteps.com. The object of research is the virtual photo exhibition “The Other Side Of Pandemic” KMJ UNISBA. The author uses qualitative research methods as a tool to complete this research case study. The data collection techniques of this research are observation, interviews, documentation, internet searching. After that, the validity of the data was tested by triangulation of sources and data collection. The purpose of this research is to determine the role, management and handling of obstacles in presenting virtual photo works. The results of this study are based on 3 simultaneous ones contained in the Social Construction Theory. Simultaneously, these are interconnected, the process of externalizing ArtSteps.com as a medium of appreciation for holding virtual exhibitions. In the process of objectification ArtSteps.com as a social product has several advantages that can be a means of support. Internalization process is a direct understanding and interpretation of an objective event as the expression of a meaning. Abstrak. Penelitian ini berlatar belakang perekembangan internet yang didukung dengan kondisi pandemic Covid-19. Dalam hal ini KMJ UNISBA mengadakan pameran foto yang diadakan secara virtual. Media yang digunakan adalah website dari ArtSteps.com. Objek penelitian pameran foto virtual “The Other Side Of Pandemic” KMJ UNISBA. Penulis menggunakan metode penelitian kualitatif sebagai alat untuk menyelesaikan studi kasus penelitian ini. Teknik pengambilan data penelitian ini yaitu observasi, wawancara, dokumentasi, internet searching. Setelah itu dilakukan uji keabsahan data dengan triangulasi sumber dan pengumpulan data. Tujuan dilakukannya penelitian ini untuk mengetahui peran, pengelolaan dan penangan kendala dalam menyajikan karya foto virtual. Hasil dari penelitian ini didasari oleh 3 simultan yang terdapat pada Teori Konstruksi Sosial. Simultan ini saling berhubungan, proses eksternalisasi ArtSteps.com sebagai media apresiasi untuk mengadakan pameran virtual. Pada proses objektivasi ArtSteps.com sebagai produk sosial memiliki beberapa kelebihan yang dapat menjadi sarana pendukung. Proses Internalisasi merupakan pemahaman dan penafsiran yang langsung dari suatu peristiwa objektif sebagai pengungkapan suatu makna.